An evaluation of the evidence brief for policy development process in WHO EVIPNet Europe countries - Adrianna Murphy; Maja Šubelj; Balázs Babarczy; Kristina Köhler; Evelina Chapman; Polonca Truden-Dobrin; Kathryn Oliver; Saskia Nahrgang; Marge Reinap; Tanja Kuchenmüller (BMC, 2022)
Abstract Background Evidence briefs for policy (EBPs) represent a potentially powerful tool for supporting evidence-informed policy-making. Since 2012, WHO Evidence-Informed Policy Network (EVIPNet) Europe has been supporting Member States in developing EBPs. The aim of this study was to evaluate the process of developing EBPs in Estonia, Hungary and Slovenia. Methods We used a rapid appraisal approach, combining semi-structured interviews and document review, guided by the Medical Research Council (MRC) process evaluation framework. Interviews were conducted with a total of 20 individuals familiar with the EBP process in the three study countries. Data were analysed thematically, and emerging themes were related back to the MRC framework components (implementation, mechanisms of impact, and context). We also reflected on the appropriateness of this evaluation approach for EVIPNet teams without evaluation research expertise to conduct themselves. Results The following themes emerged as important to the EBP development process: how the focus problem is prioritized, who initiates this process, EBP team composition, EBP team leadership, availability of external support in the process, and the culture of policy-making in a country. In particular, the EBP process seemed to be supported by early engagement of the Ministry of Health and other stakeholders as initiators, clear EBP team roles and expectations, including a strong leader, external support to strengthen EBP team capacity and cultural acceptance of the necessity of evidence-informed policy-making. Overall, the evaluation approach was considered feasible by the EBP teams and captured rich qualitative data, but may be limited by the absence of external reviewers and long lag times between the EBP process and the evaluation. Conclusions This process occurs in a complex system and must be conceptualized in each country and each EBP project in a way that fits local policy-making culture, priorities, leadership and team styles, roles and available resources. The use of a rapid appraisal approach, combining qualitative interviews and document review, is a feasible method of process evaluation for EVIPNet member countries.